Age-dependent sex differences in graft loss after kidney transplantation - Vinson, Amanda J.; Zhang, Xun; Dahhou, Mourad; Süsal, Caner; Döhler, Bernd; Sapir-Pichhadze, Ruth; Cardinal, Heloise; Melk, Anette; Wong, Germaine; Francis, Anna; Pilmore, Helen; Foster, Bethany J. (Transplantation, 2022)
Export - Background. Sex differences in kidney graft loss rates were reported in the United States. Whether these differences are present in other countries is unknown. Methods. - We estimated the association between recipient sex and death-censored graft loss in patients of all ages recorded in the Scientific Registry of Transplant Recipients, Australia and New Zealand Dialysis and Transplant Registry, and Collaborative Transplant Study registries who received a first deceased donor kidney transplant (1988-2019). We used multivariable Cox regression models, accounting for the modifying effects of donor sex and recipient age, in each registry separately; results were combined using individual patient data meta-analysis. - Results. - We analyzed 438 585 patients. Young female patients 13-24 y old had the highest crude graft loss rates (female donor: 5.66; male donor: 5.50 per 100 person-years). Among young recipients of male donors, females showed higher graft loss risks than males (0-12 y: adjusted hazard ratio [aHR] 1.42, (95% confidence interval [CI], 1.17-1.73); 13-24 y: 1.24 (1.17-1.32); 25-44 y: 1.09 (1.06-1.13)). When the donor was female, there were no significant differences by recipient sex among those of age <45 y; however, the aHR for females was 0.93 (0.89-0.98) in 45-59 y-old and 0.89 (0.86-0.93) in ≥ 60 y-old recipients. Findings were similar for all 3 registries in most age intervals; statistically significant heterogeneity was seen only among 13-24-y-old recipients of a female donor (I2 = 71.5%, P = 0.03). - Conclusions. - There is an association between recipient sex and kidney transplantation survival that is modified by recipient age and donor sex.